The dragon of Trelian - Knudsen, Michelle (Somerville, Mass. : Candlewick Press, 2009)
A mage's apprentice, a princess, and a dragon combine their strength and magic to bring down a traitor and restore peace to the kingdom of Trelian.
Booklist.
Kirkus Review.
5.7
3-6
Keywords: Dragons -- Juvenile fiction; Magic -- Juvenile fiction; Princesses -- Juvenile fiction; Dragons -- Fiction; Fantasy; Magic -- Fiction; Princesses -- Fiction; Dragons -- Fiction; Magic -- Fiction; Princesses -- Fiction; Fantastic fiction; Fantastic fiction